Analisis Bibliometrik Mesin Keripik Pisang di Indonesia Menggunakan Aplikasi Publish or Perish (PoP) dan VOSviewer - ariyanto, ariyanto; Arifin, Abdul Nasser; Sulfiana, Enni; A Assagaf, Iman Pradana; Salu, Salma; pasau, Kristiana (Journal of Energy, Materials, & Manufacturing Technology, 2024)
This bibliometric analysis study includes the publication of banana chip machines in Indonesia from 2003 to 2023. The number of studies related to this research tends to increase every year with an annual growth rate of 60.5% with a total of 989 articles. The study aims to provide insight into research trends and patterns surrounding banana chip machines in the country. A bibliometric approach is used to analyze a collection of relevant scientific articles, conference papers, and other scientific publications. The analysis covers a specific time period and investigates various dimensions, such as publication output, research collaboration, citation patterns, and keyword frequency. The findings reveal the growth and impact of research publications in the field of banana chip machines in Indonesia, highlighting key contributors and their affiliates. In addition, the study identifies emerging research topics and suggests future directions for further exploration. The results of this bibliometric analysis serve as a valuable resource for researchers, policymakers, and stakeholders interested in understanding the banana chip machine research landscape in Indonesia and making informed decisions in related fields.